Greenhouse Gas Emissions from Several Agricultural Components in Bangladesh: An Economic Study - Dr. Musfekur Rahman; Professor Dr. Md. Rabiul Rahman (Al-Qanṭara, 2023)
The global production of healthcare (medical) waste has increased due to COVID-19. Developing countries are especially impacted by this dangerous and toxic medical waste due to insufficient management mechanisms. Bangladesh has recently seen an upsurge in the production of medical waste, with an estimated 3% yearly growth rate. The concept of sustainable waste management is far behind Bangladesh's present healthcare waste management system. To create a successful waste management system, Bangladesh must apply the principles of the circular economy (CE) and life cycle assessment (LCA). Yet, the main challenges to the development of a successful medical waste management system in Bangladesh include a lack of information and study in this area. This study is given as a manual that offers an in-depth analysis of medical waste. Keywords- Greenhouse Gas Emissions, Agricultural Components, Bangladesh